The immune responses on cattle and buffaloes infected with Fasciola gigantica before and after treatment - S.E Estuningsih; S Widjajanti; Suhardono . (Jurnal Ilmu Ternak dan Veteriner, 1999)
The immune responses of cattle and buffaloes against the infection of liver flukes Fasciola gigantica were observed by ELISA. Six cattle and 6 buffaloes were infected orally with 700 metacercariae of F. gigantica, 2 cattle and 2 buffaloes were remained uninfected as control animals. Serum blood samples were collected weekly and the antibody levels were monitored before and after treatment. The results showed that the antibody level on cattle increased after 2 weeks post-infection, then gradually increased until reaching the peak at II weeks after infection. In the contrary, the antibody level on buffaloes appeared slower than on cattle, it increased after 13 weeks of infection and reach the peak at 25 weeks after infection. When the antibodylevels reach the peak, both groups of infected animals were treated with triclabendazole. After treatment, the antibody level oncattle was immediately decreased at one week of treatment, and gradually decreased up to the lowest antibody level at 7 weeks after treatment. The response of the treatment on buffaloes showed almost similar pattern, the antibody level decreased after one week of treatment, then remained constant for about 4 weeks, and reach the lowest antibody level at 7 weeks after treatment. It is concluded that the immune responses against the infection of F. gigantica in cattle and buffaloes are different, but the response of the treatment with triclabendazole are similar.   Key words: Fasciola gigantica, cattle, buffaloes, antibody levels, triclabendazole